Changes in the distribution of a spectrin-like protein during development of the preimplantation mouse embryo (The Rockefeller University Press, 1985)
The mouse blastocyst expresses a 240,000-mol-wt polypeptide that cross- reacts with antibody to avian erythrocyte alpha-spectrin. Immunofluorescence localization showed striking changes in the distribution of the putative embryonic spectrin during preimplantation and early postimplantation development. There was no detectable spectrin in either the unfertilized or fertilized egg. The first positive reaction was observed in the early 2-cell stage when a bright band of fluorescence delimited the region of cell-cell contact. The blastomeres subsequently developed continuous cortical layers of spectrin and this distribution was maintained throughout the cleavage stages. A significant reduction in fluorescence intensity occurred before implantation in the apical region of the mural trophoblast and the trophoblast outgrowths developed linear arrays of spectrin spots that were oriented in the direction of spreading. In contrast to the alterations that take place in the periphery of the embryo, spectrin was consistently present in the cortical cytoplasm underlying regions of contact between the blastomeres and between cells of the inner cell mass. The results suggest a possible role for spectrin in cell-cell interactions during early development.